A bidirectional power converter connecting electric vehicle battery and DC microgrid - Wijanarko, Sulistyo; Hasyim, Gifari Iswandi; Furqani, Jihad; Rizqiawan, Arwindra; Dahono, Pekik Argo; Muqorobin, Anwar (Institute of Advanced Engineering and Science, 2024)
One way to increase electric vehicle (EV) battery utilization is to connect it to a dc microgrid. The EV battery can assume the role of an energy storage from the grid point of view. A bidirectional DC-DC converter will be needed to transfer power between them back and forth. This paper proposes the converter design considering its functional objective, including interleaved phase number determination. Efficiency performance evaluation is presented by power loss analysis with the parasitic-parameters consideration of the components. Finding optimum switching frequency based on power loss analysis is performed independently between input and output sides of the converter. Finally, experiments using a scaled-down prototype are shown to verify the analytical analysis of the converter. The experimental results properly validate the power loss analytic analysis carried out in this paper with a maximum error of 2.04% at 1131-watt, 60 V battery voltage, and 140 V grid voltage. Maximum efficiency 96.97% is obtained at 301-watt, 130 V battery voltage, and 151 V grid voltage. Overall, the converter has a simple structure, capable to be operated in various levels of input and output voltages with a minimum battery side current ripple.